Association of M55L and Q192R polymorphisms of paraoxonase 1 gene (PON1) with recurrent pregnancy loss risk: A case-control study - Mehdi Alizadeh; Mahboobeh Nasiri; Morteza Samadi; Nasrin Ghasemi; Ali Moradi (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract Background: Recurrent pregnancy loss (RPL) refers to the incidence of two or more abortions before the first half of pregnancy. Oxidative stress has been hypothesized to play a central role in RPL. Objective: To investigate the relationship between Q192R and L55M polymorphisms of PON1 as antioxidant enzyme and the risk of RPL. Materials and Methods: In this case-control study, 110 women with RPL (case) and 110 healthy fertile women (control) referred to the Research and Clinical Center for Infertility, Shiraz, Iran were enrolled. Genomic DNA was extracted from the peripheral blood in all participants. Polymorphisms were genotyped by polymerase chain reaction-restriction fragment length polymorphism method. Results: Statistical analysis of Q192R polymorphism showed a significant difference for the RR genotype between the case and control group (OR = 11, CI = 1.39-86.87, p = 0.005) but none for the QR and QQ genotypes. No significant association was observed between the R and Q allelic frequency in the RPL participants compared to the control group (p = 0.53). Also, statistical analysis of the L55M polymorphism for MM genotype in the case group compared with the control group showed a significant difference (OR = 3.59, CI = 0.97-13.30, p = 0.042), but none for the LM and LL genotypes. Conclusion: The findings showed a significant correlation between the Q192R polymorphisms and the L55M PON1 enzyme and RPL in this study population.